National Islam vs. Transnational Islam: The War of Interpretation and Its Impact in Indonesia - Anggraeni, Bethari Ayu; Malik, Ichsan; Arbiansyah, Tri Panca Titis; Setiawibawa, Rachmat; Uksan, Arifuddin (Cita konsultindo, 2025)
Indonesia as the world’s most populous Muslim-majority nation, faces a growing ideological contest between National Islam a locally rooted, moderate, and inclusive form of Islam and Transnational Islam, which promotes a more conservative and globalized religious orientation. This study explores the dynamics of this ideological struggle and its implications for Indonesia’s socio-political stability and national security. Using a qualitative descriptive approach with library research methods, the paper analyzes the ideological differences, conflict patterns, and state as well as civil society interventions in managing tensions between these two streams. The findings show that Transnational Islam, represented by movements such as the Muslim Brotherhood, Hizbut Tahrir, and Salafi groups, often challenges Indonesia’s foundational ideology of Pancasila and promotes exclusivism that threatens social cohesion. Meanwhile, National Islam embodied by Nahdlatul Ulama and Muhammadiyah emphasizes moderation, cultural adaptation, and democracy, acting as a stabilizing force. The ideological clash manifests not only in theological debates but also in education, politics, and public discourse, sometimes escalating into violence and terrorism. Applying Social Identity Theory, Social Conflict Theory, and Coser’s Functional Theory of Conflict, this study concludes that religious identity, power struggles, and group dynamics collectively shape the conflict landscape. Effective conflict intervention requires the synergy of state policies, moderate religious movements, and community-based dialogue to promote religious moderation and maintain national unity.